PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR KOGNITIF PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Hidayah, Andini Nur; Salimi, Asmayani; Ghasya, Dyoty Auliya Vilda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
Effective learning requires media that can help students understand the material more effectively. One method that can be used is audio-visual media, which is expected to enhance students' cognitive learning outcomes, especially in Pancasila Education. This study aims to evaluate the impact of using audio-visual media on the cognitive learning outcomes of fifth-grade students at SD Negeri 35 Pontianak Selatan. This research employs a quasi-experimental method with a Nonequivalent Control Group Design. Out of three available classes, two were selected as samples using a purposive sampling technique. One class received instruction using audio-visual media (experimental group), while the other class continued with conventional teaching methods (control group). Data was collected through a cognitive learning outcome test in multiple-choice format and analyzed using parametric statistical tests to compare the learning outcomes of both groups. The results indicate that the average learning outcomes of students in the experimental group were higher than those in the control group. The t-test analysis confirmed a significant difference between the two groups, suggesting that the use of audio-visual media positively influences students' cognitive learning outcomes. Based on these findings, it can be concluded that audio-visual media has a positive impact on improving students' cognitive learning outcomes in Pancasila Education. Therefore, teachers are encouraged to utilize this media in the learning process to enhance the effectiveness and quality of classroom instruction.